EFFECT OF INOCULANT AND RAMIE COMPOST ON EFFICIENCY DEGRADATION HIDROCARBON, POPULATION TOTAL FUNGI AND RAMIE - Yuhanidz Yuhanidz; Pudjawati Suryatmana; Betty Natalie Fitriatin (Jurnal Penelitian Saintek, 2019)
This study was aimed at determining the effect of ramie, ramie compost and types of inoculants on the efficiency of hydrocarbon degradation, total fungi population, and ramie height. The study was conducted using factorial RAK with 2 factors. The calculation of the total population of Aspergillus niger was done using the total plate count (TPC) method, while the measurement of total petroleum hydrocarbons (TPH) levels used the gravimetric method. The experiment was conducted at the Greenhouse of the Faculty of Agriculture, Padjadjaran University, Jatinangor, West Java with an altitude of 822 meters above sea level. Soil analysis was carried out at the Soil Fertility and Plant Nutrition Laboratory and the Soil Biology Laboratory, Faculty of Agriculture, Padjadjaran University. The experiment was conducted from November 2017 to February 2018. The results of the study do not show an interaction between inoculants and ramie compost on the efficiency of degradation, total fungi population and ramie height in the phytoremediation process of petroleum waste. The results also showed that there was no best type of inoculant and ramie compost dose for degradation efficiency, total fungi population and ramie height in phytoremediation of petroleum waste.PENGARUH INOKULAN DAN KOMPOS RAMI TERHADAP EFISIENSI DEGRADASI HIDROKARBON, POPULASI TOTAL FUNGI DAN TINGGI RAMI Penelitian ini bertujuan untuk mengetahui pengaruh rami, kompos rami, dan jenis inokulan terhadap efisiensi degradasi hidrokarbon, populasi total fungi dan tinggi tanaman rami. Penelitian dilakukan dengan menggunakan RAK faktorial dengan 2 Faktor. Perhitungan populasi total Aspergillus niger dilakukan dengan menggunakan metode total plate count (TPC), sedangkan pengukuran kadar total petroleum hydrocarbons (TPH) menggunakan metode gravimetri. Percobaan dilaksanakan di Rumah Kaca Fakultas Pertanian Universitas Padjadjaran Jatinangor, Kabupaten Sumedang, Provinsi Jawa Barat dengan ketinggian 822 mdpl. Analisis tanah dilakukan di Laboratorium Kesuburan Tanah dan Nutrisi Tanaman dan Laboratorium Biologi Tanah Fakultas Pertanian Universitas Padjadjaran. Percobaan dilaksanakan dari bulan November 2017 sampai dengan bulan Februari 2018. Hasil penelitian tidak menunjukkan adanya interaksi antara inokulan dan kompos rami terhadap efisiensi degradasi, populasi total fungi dan tinggi tanaman rami pada proses fitoremediasi limbah minyak bumi, serta tidak diperoleh jenis inokulan dan dosis kompos rami terbaik terhadap efisiensi degradasi, populasi total fungi, dan tinggi tanaman rami pada fitoremediasi limbah minyak bumi.